8 - Lumpen Youth Culture and Political Violence: Sierra Leoneans Debate the RUF and the Civil War * - Bangura, Yusuf (Africa Development, 1997)
by C. Blake, L. Gberie, L. Johnson, K. Kallon, S. Kemokai, P. K. Muana & A. Zack- Williams